'Context, gestures, and smiles': investigating linguistic and cultural attitudes in Rick Steves's European phrasebooks. Issue 6 (2nd November 2021) - Lederman, Erica
ABSTRACT: This paper investigates linguistic and cultural attitudes found in tourist phrasebooks written by US travel writer and television host Rick Steves. Through a Critical Discourse Analysis (CDA) of Steves's European phrasebook series, it is argued that Steves portrays English speaking tourists as the dominant party in tourist-local interactions and reassures his readers that their lack of foreign language ability will not be an impediment to their travels abroad. Through the use of stereotypical descriptive adjectives and the -plurals (e.g. The French), Steves positions European languages and their speakers as monolithic, homogeneous entities. Furthermore, Steves portrays multilingualism as an expected convenience to travelers rather than as an intellectual accomplishment. This research extends on previous studies which have explored the role tourist phrasebooks play as cultural mediators [Hallett, R. W. (2017). A taste of this lively language: attitudes towards languages other than English in Lonely Planet phrasebooks. Journal of Multicultural Discourses, 12(3), 214–230; Koch, E. (2015). Mediation as Worldmaking in Tourist Phrasebooks. Journal of Language, Literature, and Culture, 62(2), 63–76]. The findings in this research will help future phrasebook authors avoid certain types of misleading or even offensive language which may deter travelers who are interested in more authentic travel experiences.